2019
DOI: 10.1039/c9tc00635d
|View full text |Cite
|
Sign up to set email alerts
|

TMC (TM = Co, Ni, and Cu) monolayers with planar pentacoordinate carbon and their potential applications

Abstract: A class of stable TMC (TM = Co, Ni, and Cu) monolayers with entirely planar pentacoordinate carbon in their ground states and their promising functional applications in spintronics, electronics, and mechanics are identified through the swarm-intelligence structure search method and first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 78 publications
1
29
1
Order By: Relevance
“…Both of them have large magnetic anisotropy energy (MAE). 15 Tang et al reported a novel planar hypercoordinate boron structure, i.e., a-FeB 3 , which is a FM metal with a Curie temperature (T C ) of 480 K and large vertical magnetic anisotropy. 16 Another issue is that only a few 2D planar hypercoordinate structures have been synthesized experimentally, hindering their applications in microelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Both of them have large magnetic anisotropy energy (MAE). 15 Tang et al reported a novel planar hypercoordinate boron structure, i.e., a-FeB 3 , which is a FM metal with a Curie temperature (T C ) of 480 K and large vertical magnetic anisotropy. 16 Another issue is that only a few 2D planar hypercoordinate structures have been synthesized experimentally, hindering their applications in microelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The same orthorhombic phase was also predicted for CoC, 21 NiC and CuC. 22 Such extension of 2D phases of 3d transition metal monocarbides (TMC) is particularly noticeable since no comprehensive data is available for their bulk phases. Experimental studies of the first half of 3d metal series are scarce, but there are reports about the formation of NaCl-type (ScC, 23 TiC, 24 VC, 24 CrC 25,26 ) or ZnS-type (MnC 27 ) bulk crystals.…”
mentioning
confidence: 60%
“…Lack of experimental reports on bulk 3d TMC formation together with recent theoretical predictions of promising 2D TMC phases raises a suggestion that some metal monocarbides might form specific planar structures rather than 3D crystals. In particular, for the reported 2D orthorhombic phases of FeC, CoC, NiC, and CuC, 18,21,22 further comprehensive studies of their stability is necessary, including an analysis of binary compositional phase TM-C diagrams.…”
mentioning
confidence: 99%
“…At 0 GPa, the TM atom loses more electrons in (HfTaZrTi)C than in (HfTaZrNb)C, which indicates that (HfTaZrTi)C has stronger ionic characteristics than (HfTaZrNb)C. The present results imply the lower stability of (HfTaZrTi)C because higher electron transfer generally results in stronger ionic bonding and is not conducive to structural stability. [ 53 ] As the pressure increases, the ionic bonds of the carbides weaken due to the slight decrease in the charge transfer from the TM atom to the C atom, indicating that the pressure is beneficial to improve the structural stability of the studied material. Moreover, compared with 0 GPa, the charge transfer of C atoms in (HfTaZrTi)C and (HfTaZrNb)C decreases by ~16.5% and 14.9% at 200 GPa, respectively, indicating that pressure has a greater effect on (HfTaZrTi)C.…”
Section: Resultsmentioning
confidence: 99%